Firm Competitiveness and the European Union Emissions Trading Scheme - Chan, Hei Sing; Li, Shanjun; Zhang, Fan (World Bank, Washington, DC, 2014)
The European Union Emissions Trading Scheme is the first international cap-and-trade program for carbon dioxide and the largest carbon pricing regime in the world. A significant concern over the Emissions Trading Scheme has been the potential impact on the competitiveness of industry. Using data on 5,873 firms in ten European countries during 2001-2009, this paper assesses the impact on three variables through which the effects on firm competitiveness may manifest -- unit material costs, employment and revenue. The analysis focuses on the three most heavily-emitting industries under the program -- power, cement, and iron and steel. Empirical results indicate that the Emissions Trading Scheme has had different impacts across these three sectors. Although no impacts are found on any of the three variables in the cement and iron and steel industries, a positive effect is found on both material costs and revenue in the power sector. The effect on material costs likely reflects fuel-switching to reduce carbon dioxide emissions, while that on revenue may be partly due to cost pass-through to consumers in a market that is less exposed to competition outside the Europen Union. Overall the findings do not substantiate concerns over carbon leakage, job loss or industry competitiveness during the study period.